2020
DOI: 10.3390/ani10122343
|View full text |Cite
|
Sign up to set email alerts
|

Selected Biological Medicinal Products and Their Veterinary Use

Abstract: Definitions of biological medicinal products (BMPs) vary depending on the source. BMPs are manufactured using complex biological/biotechnological processes involving living cell lines, tissues and organisms such as microorganisms, plants, humans and even animals. Advances in modern biotechnological methods and genetic engineering have made it possible to search for new drugs with a targeted effect and simultaneous reduction of adverse effects, which has resulted in BMPs dynamically increasing their share in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Despite these concerns, it should be clearly stated that there are both human and equine MSC clinical products produced in FBS-media that have received market approval in Europe, Canada, New Zealand, Japan, and South Korea ( 46 , 47 ). The two veterinary stem cell products currently approved by the European Medicines Agency, HorStem (EquiCord) and Arti-Cell Forte (Boehringer Ingelheim), are both composed of allogeneic equine MSCs grown in FBS.…”
Section: Fbs In Msc Culturementioning
confidence: 99%
“…Despite these concerns, it should be clearly stated that there are both human and equine MSC clinical products produced in FBS-media that have received market approval in Europe, Canada, New Zealand, Japan, and South Korea ( 46 , 47 ). The two veterinary stem cell products currently approved by the European Medicines Agency, HorStem (EquiCord) and Arti-Cell Forte (Boehringer Ingelheim), are both composed of allogeneic equine MSCs grown in FBS.…”
Section: Fbs In Msc Culturementioning
confidence: 99%
“…The residue was dried under reduced pressure over phosphorous pentoxide. 2 J HH = 13.7), 7.12 (d, 2H, Ar-H, 4 J HH = 2.3), 7.61 (d, 2H, Ar-H, 4 J HH = 2.3), 7.66 (s, 2H, Ar-H), 7.84 (s, 2H, Ar-H). 13 C NMR (CD 3 OD, δ, ppm): 27.82, 27.85, 28.00, 28.08, 28.11, 28.27, 28.37, 28.43, 30.52, 30.65, 30.68, 31.69, 31.78, 31.87, 34.48, 35.15, 35.19, 35.28, 39.97, 40.34, 40.40, 42.…”
Section: Generalmentioning
confidence: 99%
“…In recent years, research aimed at developing DNA vaccines has shown great potential [ 1 ]. These medicinal products are already successfully used in veterinary medicine [ 2 ]. Recently, Inovio Pharmaceuticals Corporation (Plymouth Meeting, PA) proposed a DNA vaccine for the prevention of SARS COVID-19 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While at-arrival management practices are somewhat dependent upon anticipated risk of BRD development, both inter- and intra-herd level disease prevalence is highly variable [5, 51]. To counter this variability, beef production systems will often administer antimicrobials and/or immunostimulants at arrival to reduce the risk of clinical BRD development and associated production losses [52, 53]. However, immunostimulant administration alone as a metaphylactic protocol for controlling BRD appears to have minimal impact on rates of morbidity [54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…To counter this variability, beef production systems will often administer antimicrobials and/or immunostimulants at arrival to reduce the risk of clinical BRD development and associated production losses [52,53]. However, immunostimulant administration alone as a metaphylactic protocol for controlling BRD appears to have minimal impact on rates of morbidity [54,55,56].…”
Section: Discussionmentioning
confidence: 99%